Wildlife Monitoring Using Camera Trap at Gunung Celering Nature Reserve Jepara Regency Central Java - Santoso, Budi; Muali, Muali; Setyo Aji, Danang (Universitas Negeri Semarang, 2025)
A wildlife monitoring survey was conducted in the Gunung Celering Nature Reserve (GCNR) located in Jepara Regency Central Java during September to November 2023 using camera traps. The survey was conducted to identify wildlife, determine the activity patterns of the wildlife in question and identify the types of wildlife protected in GCNR. The survey results showed that 868 videos were obtained with details of 173 wildlife video captures, 14 videos of human activities and 711 non-object videos. The 173 wildlife videos consisted of 14 types of wildlife consisting of 7 Aves (6 Orders, 6 Families), 5 Mammals (5 orders, 5 families), 1 Reptil and 1 Amphibian. Of the 173 wildlife videos, 7 videos were obtained from 4 species that were active at night. The remaining 166 videos were successfully documented during the day. The animals documented at night were Frogs, Civets, Jungle Cats and Rats. Of the 14 of wild animals found, there are 3 protected species based on Permenlhk 106/2018, 2 types of animals with En (endangered) status and 1 type of animal with Vul (Vulnerable) status based on IUCN as well as 3 types of animals with Appendix II category and 1 type of animal included in Appendix I CITES category.